Towards a public space. Le Corbusier and the Greco-Latin tradition in the modern city. - Sequeira, Marta (2018)
Le Corbusier is well-known for his architectural accomplishments, which have been extensively discussed in literature. Towards a Public Space instead offers a unique analysis of Le Corbusier’s contributions to urban planning. The public spaces in Le Corbusier’s plans are usually considered to break with the past and to have nothing whatsoever in common with the public spaces created before modernism. This view is fostered by both the innovative character of his proposals and by the proliferation in his manifestos of watchwords that mask any evocation of the past, like l’esprit nouveau ("new spirit") and l’architecture de demain ("architecture of tomorrow"). However, if we manage to rid ourselves of certain preconceived ideas, which underpin a somewhat less-than-objective idea of modernity, we find that Le Corbusier's public spaces not only didn't break with the historical past in any abrupt way but actually testified to the continuity of human creation over time.　 Aimed at academics and students in architecture, architectural history and urban planning, this book fills a gap in the systematic analysis of Le Corbusier’s city scale plans and, specifically, Corbusian public spaces following the Second World War.